Tobacco use among construction workers: A qualitative study exploring experiences and meaning - Hoekstra, Beverley (University of Waterloo, 2013)
While smoking prevalence among the general Canadian population has declined to 17%, declining rates have not been achieved equitably across all sub-populations (Statistics Canada, 2011). Smoking prevalence is particularly high among blue-collar workers, and individuals employed in the construction industry have the highest smoking prevalence (34%, Conference Board of Canada, 2013). Though studies have attempted to understand these disparities and how to combat them, research is necessary to understand the social contexts in which construction workers smoke. This study sought to understand these contexts by exploring experiences and meaning of smoking. Semi-structured, in-depth interviews were conducted with 14 construction workers living and working in Southern Ontario. Qualitative inductive analysis was conducted in three phases: (1) simultaneous data gathering and generating nodes, (2) coding and subgroup analysis, and (3) limited theory development. Grounded theory approach to analysis identified six main categories encompassing various subthemes. These included: day-to-day workplace experiences, experience of smoking, reasons for smoking, sociability of smoking, mechanisms associated with continued smoking, and experiences with quitting or cutting back. Sub-group analyses identified differences between participants depending on age, skill level (unskilled worker versus skilled tradesperson), and job sector (residential versus commercial/industrial). Social theories and concepts identified in the literature review were referred to, including the Social Contextual model by Sorensen and colleagues (2004). A potential set of contextual factors and modifying mechanisms that may be impacting construction worker’s tobacco use on or off jobsites are presented. The findings indicate that smoking is a complex issue among construction workers. For many, smoking goes hand-in-hand with working. Smoking is a social experience, and common on worksites. Workers experience various smoking policies on different jobsites. Policies may or may not be followed or enforced. Smoking has different meanings for different workers. However, factors external to the workplace must also be considered (e.g. partner smoking status). Supports that could be offered in workplace contexts include incentives, coverage of quitting aids, and limiting smoking (e.g. smoke-free policy). These findings have implications for policy and practice. Further research, including collaborative intervention development, is necessary to address high and persistent rates of tobacco use among construction workers.
Keywords: tobacco use; construction workers; qualitative research; cessation; Health Studies and Gerontology